2021
DOI: 10.3390/mi12091075
|View full text |Cite
|
Sign up to set email alerts
|

Neutrally Buoyant Particle Migration in Poiseuille Flow Driven by Pulsatile Velocity

Abstract: A neutrally buoyant circular particle migration in two-dimensional (2D) Poiseuille channel flow driven by pulsatile velocity is numerical studied by using immersed boundary-lattice Boltzmann method (IB-LBM). The effects of Reynolds number (25≤Re≤200) and blockage ratio (0.15≤k≤0.40) on particle migration driven by pulsatile and non-pulsatile velocity are all numerically investigated for comparison. The results show that, different from non-pulsatile cases, the particle will migrate back to channel centerline w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
3
2
0
Order By: Relevance
“…The obtained equilibrium positions (Y eq ) are tabulated in Tab. 1 and are in good agreement with the results of Huang et al [24].…”
Section: Validationsupporting
confidence: 92%
See 2 more Smart Citations
“…The obtained equilibrium positions (Y eq ) are tabulated in Tab. 1 and are in good agreement with the results of Huang et al [24].…”
Section: Validationsupporting
confidence: 92%
“…The equilibrium positions are shifted downwards and the migration times are reduced considerably when the particles Table 1. Comparison of the equilibrium positions Y eq of particles in Poiseuille flow for two diameters observed in the present work with those found in [24] (Re = 50.0).…”
Section: Migration Of Non-neutrally Buoyant Particlessupporting
confidence: 51%
See 1 more Smart Citation
“…The validity of the SPH method is demonstrated by simulating the sedimentation of a circle based on the open-source library SPHinXsys (Zhang et al 2021b), using the same setup as Hashemi et al (2012) as shown in figure 1. To compare the results, the LBM is also utilized, which has been previously validated in our work (Huang et al 2021). Figure 2 shows that the vertical position Y p and settling velocity V y of the circle over time match well with both the results of LBM and those reported by Hashemi et al (2012) and (Glowinski et al 2001).…”
Section: Validationsupporting
confidence: 60%
“…For an efficient evaluation of the flow and pressure distributions in a microchannel network, Zhao et al [ 7 ] introduced an electric circuit analogy and applied it to study the effect of microchannel length on the flow behaviors. Another interesting study is presented by Huang et al [ 8 ], where the immersed boundary method has been combined with the lattice Boltzmann method to study the trajectory of a neutrally buoyant circular particle in the pulsatile channel flow. The particle exhibits rich dynamic behaviors which have not been observed in non-pulsatile situations, and the results could be useful for nanoparticle transport in drug delivery applications.…”
mentioning
confidence: 99%